“The Mystery of the Cell Kingdom”: an online game to improve the learning of thyroid physiology - Cardinali, Camila Aparecida Errerias Fernandes; Martins, Yandara Akamine; Prates, Rodrigo Pereira; Araújo, Emmanuel Veríssimo de; Viana, Felipe Jose Costa; Sousa, Maria Eleticia de; Bombardi, Eduardo da Cunha [UNESP]; Baldo, Marcus Vinicius Chrysostomo; Nunes, Maria Tereza (American Physiological Society, 2025)
Games and analogies can significantly enrich the learning experience when integrated with traditional expository teaching methods. With this aim, we developed “The Mystery of the Cell Kingdom,” an online game designed to enhance understanding of the physiology of thyroid hormones through a medieval analogy. In the game, students are challenged to apply their knowledge of endocrine physiology to solve a series of relevant questions on the topic. The main objective of this study was to evaluate the effectiveness of the game as a complementary review tool for a theoretical lesson on thyroid hormones. After an online class, 18 students participated in the game and completed questionnaires before and after the activity. The results showed a 14.9% increase in postgame scores. Feedback revealed that all students enjoyed the experience and provided positive evaluations of both the game and the analogy used. These findings suggest that the online game The Mystery of the Cell Kingdom can facilitate learning about thyroid hormones while offering an engaging, enjoyable, and motivating approach to physiology education. NEW & NOTEWORTHY “The Mystery of the Cell Kingdom” is an online game designed as a revision tool of thyroid hormone endocrine physiology. There is a shortage of knights in the Cell Kingdom and you are called as a historian specialist in the Middle Ages to help solve the mystery. Can you help?
Keywords: educational game; endocrine physiology; gamification; physiology education